EFL LEARNERS’ COMPREHENSION OF EXTENSIVE READING BASED ON HIGHER ORDER THINKING SKILLS. - Trisha Fitri Pramaysella; Nani Ronsani Thamrin; Endang Darsih (Journey: Journal of English Language and Pedagogy, 2023)
This study, conducted at a private university in Kuningan, West Java, aimed to understand the comprehension of learners based on Higher Order Thinking Skills (HOTS) in Extensive Reading classes as well as to identify the reasons why some students find it challenging to understand reading based on HOTS in these classes. The three steps of the HOTS definition by Anderson and Krathwohl (2001) were analysis (C4), evaluation (C5), and creation (C6). The research is descriptive-qualitative, and the methods for gathering data include interviewing and observation. Second-semester students at a private university in Kuningan, West Java, served as the study's subjects. The observation's findings showed that the majority of second-semester students were capable of analyzing the information (Analyzing, C4), evaluating the text's main ideas (Evaluating, C5), and coming up with new ideas to use in other situations (Creating, C6), whether outside of the classroom or on other occasions. Moreover, based on the results of interviews with 10 students in the classroom, there were 5 main factors that affect the students’ reading comprehension based on HOTS which were: lack of vocabulary, lack of focus, lack of time, not having basic knowledge and not interesting in reading